ATP1A2- and ATP1A3-associated early profound epileptic encephalopathy and polymicrogyria - Vetro, Annalisa; Nielsen, Hang N; Holm, Rikke; Hevner, Robert F; Parrini, Elena; Powis, Zoe; Møller, Rikke S; Bellan, Cristina; Simonati, Alessandro; Lesca, Gaétan; Helbig, Katherine L; Palmer, Elizabeth E; et al. (Brain, 2021)
Constitutional heterozygous mutations of ATP1A2 and ATP1A3, encoding for two distinct isoforms of the Na+/K+-ATPase (NKA) alpha-subunit, have been associated with familial hemiplegic migraine (ATP1A2), alternating hemiplegia of childhood (ATP1A2/A3), rapid-onset dystonia-parkinsonism, cerebellar ataxia-areflexia-progressive optic atrophy, and relapsing encephalopathy with cerebellar ataxia (all ATP1A3). A few reports have described single individuals with heterozygous mutations of ATP1A2/A3 associated with severe childhood epilepsies. Early lethal hydrops fetalis, arthrogryposis, microcephaly, and polymicrogyria have been associated with homozygous truncating mutations in ATP1A2. We investigated the genetic causes of developmental and epileptic encephalopathies variably associated with malformations of cortical development in a large cohort and identified 22 patients with de novo or inherited heterozygous ATP1A2/A3 mutations. We characterized clinical, neuroimaging and neuropathological findings, performed in silico and in vitro assays of the mutations’ effects on the NKA-pump function, and studied genotype-phenotype correlations. Twenty-two patients harboured 19 distinct heterozygous mutations of ATP1A2 (six patients, five mutations) and ATP1A3 (16 patients, 14 mutations, including a mosaic individual). Polymicrogyria occurred in 10 (45%) patients, showing a mainly bilateral perisylvian pattern. Most patients manifested early, often neonatal, onset seizures with a multifocal or migrating pattern. A distinctive, ‘profound’ phenotype, featuring polymicrogyria or progressive brain atrophy and epilepsy, resulted in early lethality in seven patients (32%). In silico evaluation predicted all mutations to be detrimental. We tested 14 mutations in transfected COS-1 cells and demonstrated impaired NKA-pump activity, consistent with severe loss of function. Genotype-phenotype analysis suggested a link between the most severe phenotypes and lack of COS-1 cell survival, and also revealed a wide continuum of severity distributed across mutations that variably impair NKA-pump activity. We performed neuropathological analysis of the whole brain in two individuals with polymicrogyria respectively related to a heterozygous ATP1A3 mutation and a homozygous ATP1A2 mutation and found close similarities with findings suggesting a mainly neural pathogenesis, compounded by vascular and leptomeningeal abnormalities. Combining our report with other studies, we estimate that ∼5% of mutations in ATP1A2 and 12% in ATP1A3 can be associated with the severe and novel phenotypes that we describe here. Notably, a few of these mutations were associated with more than one phenotype. These findings assign novel, ‘profound’ and early lethal phenotypes of developmental and epileptic encephalopathies and polymicrogyria to the phenotypic spectrum associated with heterozygous ATP1A2/A3 mutations and indicate that severely impaired NKA pump function can disrupt brain morphogenesis.